Stress-strain model for partial CFRP confined concrete - Ferreira, Débora (2011)
The Harajli et al. analytical model was modified in order to predict the compression stress-strain behaviour of reinforced concrete column elements partially and totally confined by CFRP lay-up sheets. The main results of the experimental program are hereby presented and analysed. The model’s performance is assessed using the experimental results.